A Challenge to Polio Eradication: Need to Replace OPV with IPV - Kaur , Sharanjit; Sharma , Anand; Singh , Harinder Jot (Current Practice in Medical Science Vol. 10, 2022)
Introduction: Vaccine virus spread is a greatest liability of OPV. On replication in vaccine recipients (usually after the first dose) or their contacts, vaccine virus can revert to neurovirulence and cause vaccine associated paralytic poliomyelitis (VAPP). Objective: Global cessation of OPV use will prevent the threat posed by Vaccine derived polioviruses in the post eradication era. And will be essential to protect the gains achieved by global eradication of wild polioviruses. In 2012, India crossed a major milestone when the World Health Organization removed it from the list of polio endemic countries after a year without a single case of polio. The presence of virus in sewage samples collected from Hyderabad was a great challenge to the March 2014 declaration "India as a polio-free nation from wild polio virus transmission". OPV use is associated with the rare occurrence of genetically drifted vaccine-derived polioviruses (VDPVs) that can circulate in under vaccinated and immunodeficient individuals. This posed a potential longer-term risk to global polio eradication program [1]. With due consideration to the presence of virus in the environment, it is time for India to rewire its strategic action plans to fight back against polio. The "endgame" for global poliomyelitis eradication will necessitate a phased withdrawal of oral poliovirus vaccine (OPV) for various strains in all countries, followed by a switch to IPV to avoid the risk of vaccine-derived polioviruses—exposing some populations to the risk of poliovirus outbreaks.